Acceleration Performance Analysis of Power-split Hybrid Powertrain System - Peng Hao; Hongyu Zhu; Chen Wang; Huijun Cheng; Haisheng Yu (Jixie chuandong)
To fulfill the design goal of acceleration performance of a power-split hybrid vehicle，constraint matrices of all possible configurations of power-split hybrid powertrain system that can be constructed by two-planetary-gear system are derived and screened. A systematic solution to the maximum output torque of all types of two planetary gear power-split systems is introduced. Base on the solution，the 100 km acceleration performance of the derived configurations are simulated，so that the optimal configuration is found.